PENGEMBANGAN ASPEK SOSIAL ANAK USIA 5-6 TAHUN MELALUI PERMAINAN TRADISIONAL DI PAUD SANTU YOSEF KECAMATAN LANGKE REMBONG - Sarinastitin, Elisabeth (incrementapedia, 2019)
Social aspects of early childhood is something important to be developed in addition to cognitive and emotional aspects. There are many ways to help the child's social development process. One of them is through traditional games. Traditional games are local games that are usually played by children as a way to gather, communicate and interact with one another. This study aims to determine whether traditional games can help social development of children specifically aged 5-6 years. The object of research is children aged 5-6 years and teachers who teach traditional games in PAUD St. Yosef Langke Rembong. The research method used is descriptive analytical of the results of direct observation when children play traditional games and interviews with teachers. The results showed that the traditional games taught and played by children at the age of 5-6 years at the PAUD St. Yosef can help improve children's social development.